Communication Between Medical Teams During Crises: The Impact of Internal Coordination in Hospitals - Mishal Suleiman Al-Abdulqader, Muath Ahmad Alturaiqy, Abdulrahim Nasser Alfawzan, ‏Saleh Abdulwahab Saleh Althunayyan, Musaed Bader Alharbi; Ghonaim Suliman Alsaif, Mohammed Saud almutairi, Fawaz lafa almutiri, Thamer Zaid Sh Alresheedi, Abdullah mohammedfehed al dajani (Journal of International Crisis and Risk Communication Research, 2024)
Purpose:The purpose of this study is to examine the impact of internal communication and coordination among medical teams during health crises in hospitals. It aims to identify how effective communication between doctors, nurses, and administrative staff influences hospital response during emergencies, and to highlight the role of technology in improving coordination. The study will provide recommendations to enhance internal communication strategies, optimize crisis management, and improve patient outcomes.Methods: This study was conducted using a quantitative research approach, focusing on a sample of 30 healthcare professionals from various departments (e.g., emergency, critical care, nursing, and administration) in a hospital setting. Participants were selected based on their direct involvement in patient care and crisis management during health emergencies.Findings:The results of the study revealed that effective communication and good internal coordination among medical teams in hospitals during crises significantly contribute to improved performance and a reduction in medical errors. It was found that good coordination between doctors, nurses, and administrative staff leads to faster healthcare delivery and improved patient outcomes. The study also identified several challenges faced by medical teams, such as lack of technological resources and unclear roles and responsibilities, which hinder effective coordination and impact the efficiency of communication between teams during crises.Conclusion:This study highlights the critical role of effective communication and internal coordination among medical teams in hospitals, particularly during health crises. The findings underscore that a well-coordinated team can significantly improve hospital performance, reduce medical errors, and enhance patient outcomes. The research also reveals several challenges, including technological limitations and unclear roles, which hinder effective communication and coordination. However, the use of technology (e.g., electronic systems, apps) has proven to be a key tool in facilitating better communication, reducing errors, and streamlining decision-making processes in high-pressure environments. Additionally, the study emphasizes the value of experience in crisis management. Medical teams with more experience in handling emergencies demonstrated more efficient coordination and quicker decision-making, which ultimately improved the overall response to the crisis. Considering these findings, it is recommended that hospitals invest in improving communication tools, clarifying roles, and training healthcare staff to enhance their crisis response capabilities. By focusing on these areas, hospitals can better navigate future crises, ensuring faster and more effective care for patients.